(NgENETIKO(B-(NFIZIOLOGI^ESKIE OSNOWY SELEKCII OZIMOJ MQGKOJ P[ENICY (B:s (NsBORNIK NAU^NYH TRUDOW (B/s - (NbIR@KOW(B, (Ns(B.(Nw(B.s; (NwSESO@ZNYJ SELEKCIONNO(B-(NGENETI^ESKIJ INSTITUTs; (NwSESO@ZNAQ AKADEMIQ SELXSKOHOZQJSTWENNYH NAUK IMENI w(B.(Ni(B. (NlENINAs ((NoDESSA (B:s (Nwsgi(B,s, 1991)
(NrEZ@ME S(B. : 96-104 (NNA RUS(B. (NI INOSTR(B. (NQZ(B.s
(NlIT(B. (NPOSLE KAVDOJ GLAWYs
Keywords: (NhLEBNYE ZLAKI I ZERNOWYE KULXTURYs; (Np[ENICAs